2019
DOI: 10.3390/colloids3040062
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Surface Charge Modification of Carbonates in Aqueous Electrolyte Solutions

Abstract: The influence of different types of salts (NaCl, CaCl 2 , MgCl 2 , NaHCO 3 , and Na 2 SO 4 ) on the surface characteristics of unconditioned calcite and dolomite particles, and conditioned with stearic acid, was investigated. This study used zeta potential measurements to gain fundamental understanding of physico-chemical mechanisms involved in surface charge modification of carbonate minerals in the presence of diluted salt solutions. By increasing the salt concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 72 publications
(138 reference statements)
4
41
0
Order By: Relevance
“…Zeta potential is also an important factor that may influence the stability and in vivo behaviour of SLN [55] . The formulation shows negative zeta potential of -18.30±0.14 mV which may be due to the SA [56] . The higher values of zeta potential enhance the stability of SLN by increasing the repulsion of particle, and thereby preventing aggregation [55] .…”
Section: Resultsmentioning
confidence: 96%
“…Zeta potential is also an important factor that may influence the stability and in vivo behaviour of SLN [55] . The formulation shows negative zeta potential of -18.30±0.14 mV which may be due to the SA [56] . The higher values of zeta potential enhance the stability of SLN by increasing the repulsion of particle, and thereby preventing aggregation [55] .…”
Section: Resultsmentioning
confidence: 96%
“…( (Derkani et al 2019), lowering the ionic strength values can enhance the water-wetness condition of the rock surface. Our results illustrate that although the ionic strength increases, the contact angle decreases.…”
Section: Effect Of Pgsw With Different Salinities On Contact Angle and Zeta Potentialmentioning
confidence: 99%
“…Adsorption of proton from solution under conditions of low pH. For instance, the experimental results of Derkani et al, (2019) (Derkani, et al, 2019) showed that an increase in concentration of monovalent salt solution (NaCl) results in negative surface charges for both calcite and dolomite particles, but it becomes less negative and its magnitude reduces toward zero with increasing concentration. Generally, low surface potential in geologic or colloidal systems develop due to two main reasons: low surface charge density of ionizable surface groups, for instance, amorphous silica (Zhuravlev , 2000) (Zhuravlev L. , 2000).…”
Section: Low Surface Potential In Colloidal Systemsmentioning
confidence: 99%